A Case Report on Lower Urinary Tract Infection in Persian Cat at Sylhet (Research in Agriculture Livestock and Fisheries, 2025)
Small animals are increasingly kept as companion animals and are often fed diverse diets with varying nutritional quality, which may predispose them to metabolic and urinary disorders. Concurrent infection of the urinary bladder and urethra is termed lower urinary tract infection (LUTI) and is characterized by clinical signs such as dysuria, hematuria, stranguria, and periuria. This case report aims to highlight the importance of proper management practices alongside medical treatment in reducing disease progression and improving quality of life. A 3.5-year-old Persian cat weighing 4.1 kg was presented to Pet and Vet Care, Sylhet, with complaints of dysuria, vomiting, constipation, and lateral recumbency. Physical examination revealed marked enlargement of the urinary bladder and kidneys, approximately four to five times normal size. Red-colored urine was evacuated by catheterization followed by cystocentesis. Urine samples were subjected to physical, chemical, microscopic, and biochemical analyses for confirmatory diagnosis. Urinalysis revealed hematuria with low specific gravity (1.012), indicating possible renal tubular damage. The presence of protein, ketone bodies, pus cells, and elevated urobilinogen (2 mg/dL) suggested renal involvement. Significantly elevated urine creatinine (86.6 mg/dL) and urine protein (486.1 mg/dL), compared with reference values, further confirmed LUTI with renal impairment. Based on clinical history, physical findings, and laboratory results, the condition was diagnosed as LUTI. This case highlights that effective management of feline LUTI requires not only appropriate therapeutic intervention but also accurate laboratory-based diagnosis and dietary management to ensure faster recovery and improved overall health.Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 507-515